Legal Safeguards for Justice Collaborators in Murder Cases: The Richard Eliezer Verdict Analysis - Charles Ardani; Sri Astutik; Vieta Imelda Cornelis; Siti Marwiyah; Bachrul Amiq (PT. Banjarese Pacific Indonesia, 2025)
Justice collaborators, or